Platform Layanan Ekonomi Berbagi: Studi Kualitas Layanan dan Kepercayaan terhadap Keberlanjutan Penggunaan dengan Religiusitas sebagai Moderasi - Amanda, Syafira; Sari, Nurma (JESI (Jurnal Ekonomi Syariah Indonesia), 2021)
This study aims to measure the effect of service quality and trust towards the continuance intention of sharing economy service platforms moderated by the religiosity variable. The object of research are the undergraduate students of Syiah Kuala University in Banda Aceh with a sample data that collects 100 respondents using the proportionate stratified random sampling method. The research was conducted partially and simultaneously. Collected data were analyzed using multiple linear regression analysis and moderated regression analysis. The results show that service quality and trust have a significant silmutaneous and partial effect on the continuance intention of sharing economy service platforms. Next, religiosity negatively moderates the relationship of trust towards the continuance intention of sharing economy service platforms in Banda Aceh City.